THE EFFECT OF MINDFULNESS BASED STRESS REDUCTION (MBSR) ON THE INTENSITY OF DYSMINORE IN ADOLESCENTS AT THE PUNGGING PUBLIC HEALTH CENTER, MOJOKERTO DISTRICT - Naning Puji Suryantini (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Lower back pain is the most common form of discomfort during pregnancy experienced by mothers, especially in the second and third trimesters. Hormonal changes, weight gain, and biomechanical adaptations of the body are the main factors causing this complaint. The impact is not only pain but also disrupts daily activities, sleep quality, and increases stress. Pharmacological management is not always safe, so non-pharmacological interventions are more recommended. One potential method is pregnancy massage with stimulation of the BL40 (Weizhong) acupressure point, which works to relax muscles, improve circulation, and stimulate the release of endorphins. This study used a quasi-experimental design with a pretest–posttest without a control group. The sample consisted of 30 pregnant women in their second and third trimesters who experienced lower back pain and received antenatal care at the Sujiati Nur Elys TPMB, Dlanggu District, Mojokerto Regency. The intervention was given three times a week, with pain measured using the Numeric Rating Scale (NRS). The results showed that before the intervention, the majority of respondents experienced severe pain (53.3%), while after the intervention, none experienced severe pain. A total of 26.7% of respondents had no pain, 53.3% had mild pain, and 20% had moderate pain. The Wilcoxon test showed p = 0.000 (p < 0.05), indicating a significant difference before and after the intervention. Thus, pregnancy massage at the BL40 point has been proven effective in reducing lower back pain in pregnant women.